Comprehensive assessment of Mahaim accessory pathways' anatomic distribution. Issue 1 (January 2022) - Gormel, Suat; Yasar, Salim; Yildirim, Erkan; Asil, Serkan; Baris, Veysel Ozgur; Gokoglan, Yalcın; Celik, Murat; Yuksel, Uygar Cagdas; Vurgun, Veysel Kutay; Kabul, Hasan Kutsi; Kose, Sedat
Objective: To present the authors' experience of Mahaim-type accessory pathways (MAPs), focusing on anatomic localizations. Methods: Data from consecutive patients who underwent electrophysiological study (EPS) for MAP ablation in two tertiary centres, between January 1998 and June 2020, were retrospectively analysed. Results: Of the 55 included patients, 27 (49.1%) were male, and the overall mean age was 29.5 ± 11.6 years (range, 12–66 years). MAPs were ablated at the tricuspid annulus in 43 patients (78.2%), mitral annulus in four patients (7.3%), paraseptal region in three patients (5.5%), and right ventricle mid-apical region in five patients (9.1%). Among 49 patients who planned for ablation therapy, the success rate was 91.8% (45 patients). Conclusion: MAPs were most often ablated at the lateral aspect of the tricuspid annuli, sometimes at other sides of the tricuspid and mitral annuli, and infrequently in the right ventricle. The M potential mapping technique is likely to be a useful target for ablation of MAPs.